Violation of the Prudential Principle in Cooperative Credit Granting - Thalib, Prawitra; Salsabila, Syauqina Maghfirah; Rahadi, Alifia Putri (RSF Conference Series: Business, Management and Social Sciences, 2024)
This research examines the violation of the prudential principle in credit granting by cooperatives from a normative legal perspective. The research aims to analyze the legal framework governing the prudential principle in cooperative credit granting, identify common forms of violations, and formulate legal implications and recommendations to strengthen the application of this principle. The research method used is normative juridical with statutory and conceptual approaches. The results show that although regulations governing the prudential principle in cooperative credit granting exist, their implementation still faces significant challenges. Common forms of violations include negligence in credit analysis, weak monitoring systems, and conflicts of interest in decision-making. The legal implications of these violations range from administrative sanctions to criminal charges for involved cooperative officials. This research recommends strengthening the regulatory framework, enhancing supervisory capacity, and reforming cooperative governance to prevent future violations of the prudential principle. In conclusion, enforcing the prudential principle in cooperative credit granting requires a comprehensive approach involving regulatory reform, institutional strengthening, and increasing legal awareness among cooperative actors.